THE POTENCY OF CALABUR TREE (Muntingia calabura) LEAF EXTRACT TO CONTROL ANTHRACNOSE OF PAPAYA FRUIT - ., Efri; Aeny, Titik Nur; ., Ivayani; Hulfa, Meisroyatul (Universitas Lampung, 2020)
The potency of calabur tree (Muntingia calabura) leaf extract to control anthracnose of papaya fruit. The papaya anthracnose caused by Colletotrichum gloeosporioides is one of the factors causing a decrease in papaya production. The research aimed to determine the abilty of calabur tree leaf extract in inhibiting growth, sporulation, and viability of C. gloeosporioides as well as incubation period and disease severity on the fruit of papaya. The experiment was arranged in a nested design, the concentrations (0, 10, 20, 30, 40, 50, and 60%) were nested within the calabur tree leaf extract methods (boiling and fractionation). The results showed that boiled calabur leaves extract was more effective than fractionated calabur leaves extract to inhibit growth of C. gloeosporioides. Boiled calabur leaves extract and fractionated leaves extract at various concentration showed capability to inhibit the growth, sporulation and viability of C. gloeosporioides. Boiled calabur leaves extract at different concentration levels were able to suppress disease development of papaya anthracnose disease on papaya fruit. The higher concentration of calabur leaves extract, are more effective to inhibit C. gloeosporioides.